2020
DOI: 10.3389/fphys.2020.00177
|View full text |Cite
|
Sign up to set email alerts
|

Protective Properties of FOXO1 Inhibition in a Murine Model of Non-alcoholic Fatty Liver Disease Are Associated With Attenuation of ER Stress and Necroptosis

Abstract: The pathogenesis of non-alcoholic fatty liver disease is currently unclear, however, lipid accumulation leading to endoplasmic reticulum stress appears to be pivotal in the process. At present, FOXO1 is known to be involved in NAFLD progression. The relationship between necroptosis and non-alcoholic steatohepatitis has been of great research interest more recently. However, whether FOXO1 regulates ER stress and necroptosis in mice fed with a high fat diet is not clear. Therefore, in this study we analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Blockade of FOXO1 has been shown to reduce phenotypes of NAFLD and NASH, including endoplasmic reticulum stress, ALT, AST, triglycerides, and body weight. 38 An impact on FOXO1 phosphorylation has previously been demonstrated after treatment with a CB1R inverse agonist in a DIO mouse model, 39 and our results expand on additional impacts of CB1R activity on Foxo1 gene expression level. Therefore, CB1R antagonism appears to reduce de novo lipogenesis associated genes and this observation provides a mechanistic rationale for the development of this class of compounds for liver diseases.…”
Section: ■ Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Blockade of FOXO1 has been shown to reduce phenotypes of NAFLD and NASH, including endoplasmic reticulum stress, ALT, AST, triglycerides, and body weight. 38 An impact on FOXO1 phosphorylation has previously been demonstrated after treatment with a CB1R inverse agonist in a DIO mouse model, 39 and our results expand on additional impacts of CB1R activity on Foxo1 gene expression level. Therefore, CB1R antagonism appears to reduce de novo lipogenesis associated genes and this observation provides a mechanistic rationale for the development of this class of compounds for liver diseases.…”
Section: ■ Discussionsupporting
confidence: 78%
“…We additionally observed significant impacts on expression of genes that drive steatosis, Foxo1 and Pparg . Blockade of FOXO1 has been shown to reduce phenotypes of NAFLD and NASH, including endoplasmic reticulum stress, ALT, AST, triglycerides, and body weight . An impact on FOXO1 phosphorylation has previously been demonstrated after treatment with a CB1R inverse agonist in a DIO mouse model, and our results expand on additional impacts of CB1R activity on Foxo1 gene expression level.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study showed that Foxo1 OE resulted in TG accumulation 32 . Furthermore, the expression of Foxo1 is upregulated in the liver of humans and mice with NAFLD 33 , 34 . Based on these observations, we determined whether Kindlin-2 modulates Foxo1 expression in hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The destruction of membrane integrity during necroptosis releases various proinflammatory mediators and promotes the progression of MAFLD [ 53 ]. Ding et al found that AS1842856 improves MAFLD by inhibiting forkhead box protein O1 (FOXO1), ERS and necroptosis [ 54 ]. TNF-α-mediated necroptosis is widely recognized as the most classical pathway.…”
Section: Mafld and Necroptosismentioning
confidence: 99%